2018
DOI: 10.1159/000491708
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Prevalence, and Duration of Chronic Kidney Disease in Taiwan: Results from a Community-Based Screening Program of 106,094 Individuals

Abstract: Background/Aims: Taiwan has the highest incidence of end-stage renal disease, which requires renal replacement therapy. Chronic kidney disease (CKD) contributes to this burden. However, the current data on the epidemiologic features of CKD in Taiwan are incomplete. Therefore, we aimed to investigate the prevalence and incidence of CKD in a population-based study and then estimate the average dwelling time (ADT) in the main clinical burden of CKD (stages 3–5). Methods: A prospective cohort study was designed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 37 publications
(47 reference statements)
0
67
2
1
Order By: Relevance
“…The differences were related to differences in the disease's nature and in the healthcare environment. First, in Taiwan, the incidence of CKD [22] and the prevalence of end-stage renal disease [23] are both much higher compared with those of other countries. Renal disease is a major financial burden for the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…The differences were related to differences in the disease's nature and in the healthcare environment. First, in Taiwan, the incidence of CKD [22] and the prevalence of end-stage renal disease [23] are both much higher compared with those of other countries. Renal disease is a major financial burden for the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Analiza svih dobijenih rezultata tokom skrininga tri grupe ispitanika sa povećanim rizikom za hroničnu bolest bubrega je pokazala da albuminuriju i/ili smanjenu JGF, dva glavna biomarkera oštećene funkcije bubrega je imalo 90,03% bolesnika sa hipertenzijom, 93,33% bolesnika sa dijabetesom i 75% bolesnika starijih od 60 godina. Ovo je daleko veći procenat od onog opisanog u beogradskim studijama i drugim sličnim studijama [3,11,15,16]. Ova razlika može da bude posledica i nekoliko nedostataka ove studije.…”
Section: Diskusijaunclassified
“…The rising prevalence of chronic kidney disease (CKD) has become a global serious health problem, especially in Taiwan, in which the estimated prevalence of total CKD and CKD stages 3-5 were 15.5% and 9.1%, respectively, according to a cohort study in 2018 [1], similar to the reported global prevalence (13.4% and 10.6%) [2]. Furthermore, Taiwan has had the highest incidence of end-stage renal disease (ESRD) in the world since 2000 [3,4].…”
Section: Introductionmentioning
confidence: 99%